A Sustainable NH4+ Ion Battery by Electrolyte Engineering. Issue 51 (22nd November 2022) - Tian, Zhengnan; Yin, Jun; Guo, Tianchao; Zhao, Zhiming; Zhu, Yunpei; Wang, Yizhou; Yin, Jian; Zou, Yeguo; Lei, Yongjiu; Ming, Jun; Bakr, Osman; Mohammed, Omar F.; et al.
Abstract: Aqueous ammonium ion battery is a promising sustainable energy storage system. However, the side reactions originating from electrolytes (the water decomposition and host material dissolution) preclude its practical applications. Unlike the metal‐based aqueous batteries, the idea of "ultrahigh concentrated electrolyte" is not feasible due to the strong hydrolysis of ammonium ions. Therefore, we propose an effective and sustainable strategy for the water hydrogen bond network modulation by adding sucrose into the electrolytes. The sucrose can form sucrose‐water hydrogen bond networks to break the continuous water hydrogen bond network, thereby inhibiting water decomposition significantly. Moreover, the weak hydrogen bond interaction between ammonium and sucrose facilitates rapid ion migration, leading to an improved ionic conductivity. This work presents a new electrolyte modulating strategy for the practical application of aqueous ammonium ion batteries. Abstract : We propose an effective and sustainable strategy for the water hydrogen bond network modulation by adding sucrose into the electrolytes. The sucrose can form sucrose‐water hydrogen bond networks to break the continuous water hydrogen bond network, thereby inhibiting water decomposition. Moreover, the weak hydrogen bond interaction between ammonium and sucrose facilitates ion migration, leading to an improved ionic conductivity.